Training of young researchers in Colombia: Reflections from the experience of the GREICI project. - Duarte-Castro, Andrés (2022)
The Young Researchers and Innovators program of the Administrative Department of Science, Technology, and Innovation - Colciencias, currently the Ministry of Science of Colombia, seeks the social appropriation of knowledge, motivating scientific vocation in young people, through training processes in research and innovation. According to the opportunities for the region to train in research from early education and to formalize the model of accompaniment of mentoring, a training experience was developed based on the mentoring model that suggested some conceptual and methodological bases to learn to investigate. The training put into practice the design of the methodology of the research project, through the "learn-doing" teaching modality, applying conceptual training during the process. Simultaneously, knowledge about the importance of transparency, rigor and responsibility from the design to the execution of the research project was expanded. The recognition of institutional support and the mentoring model as fundamental pillars of the experience. Aspects of the young researcher and mentors are required to motivate the scientific vocation in a research training experience.